Du bricolage à la prescription : évolution du rôle des acteurs de l’informatique scolaire - François Villemonteix (Recherches en Éducation)
Since the 80s, the French educational system has temporarily appointed teachers for the promoting the uses of computers in elementary schools, the “ATICE” (Animateurs pour les Technologies de l’Information et de la Communication en Education), in charge of advising schools, training teachers,taking care of project management, maintenance and technology watch. Their professional activity is therefore manifold and changing, defined by the current institutional priorities. It is also characterized by unusual statutory conditions. The function of ATICE, in search for legitimacy, is torn between educational advice, professional development of their colleagues and technical expertise. It relies on expert knowledge, on skills essentially built on contextual experience. On the educational side, their domain of expertise is mainly technical - and particularly discussed on line within the community since they work in a very competitive field of practice. This expertise places the ATICE in an overhanging position compared to the other actors of the field and offers another guarantee of survival to their function. The very reactive list of discussion is a privileged place for professional socialization. It plays an important part for the dissemination of institutional prescriptions. Rather centred on technical questions, it is a melting pot for the expert practice that the ATICE try to negotiate with the institution in exchange value. Little theorized, the exchanges leave only a small place to didactic questions pertaining to educational instrumentation at school and to the formation of the teachers. More generally, in a context of a still uncertain definition of what ICT at school really is, the ATICE represent, for the national institution, a flexible population, capable of adapting to the new requirements of the successive reforms. A stable status of these members of the staff doesn’t seem to be compatible with the requirements of the institution.